2022
DOI: 10.21203/rs.3.rs-1682290/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compound heterozygous deletions of the WWOX gene caused a WOREE syndrome associated with severe epileptic encephalopathy

Abstract: Recent studies showed that germline, bi-allelic and pathogenic variants of the WWOX gene have been associated with spinocerebellar ataxia type 12 (SCAR12) and a severe WWOX-related epileptic encephalopathy (WOREE syndrome). The underlying mechanisms of the diseases are poorly understood. Here, we reported the case of a WOREE syndrome patient with early-onset refractory seizures and global neurodevelopmental delay who died at the age of two and a half years. The whole exon sequencing showed homozygous exon 6 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This observation allowed the authors to propose that Wwox is involved in the oligodendrocyte differentiation and the myelination process [57]. A magnetic resonance imaging (MRI) of WOREE patients' brains besides the varying brain structural defects usually shows also reduced myelination [13,[65][66][67][68]. Currently, the specific neuronal deletion of murine Wwox which generates phenotypes that resemble what is observed in WOREE patients was characterized by a significant decrease in transcript levels of genes involved in myelination in the mouse cortex and hippocampus and reduction of myelinated axons [61].…”
Section: The Wwox Gene Modulates Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation allowed the authors to propose that Wwox is involved in the oligodendrocyte differentiation and the myelination process [57]. A magnetic resonance imaging (MRI) of WOREE patients' brains besides the varying brain structural defects usually shows also reduced myelination [13,[65][66][67][68]. Currently, the specific neuronal deletion of murine Wwox which generates phenotypes that resemble what is observed in WOREE patients was characterized by a significant decrease in transcript levels of genes involved in myelination in the mouse cortex and hippocampus and reduction of myelinated axons [61].…”
Section: The Wwox Gene Modulates Lipid Metabolismmentioning
confidence: 99%
“…It has been shown that increasing glycolysis may slow neurodegeneration [100]. WWOX has been also implicated in epilepsy [61,68]. It was observed that the anaerobic glycolysis and concentration of lactate in the epileptogenic brain increased in comparison to the control [101].…”
Section: Participation Of Wwox In Glucose Metabolismmentioning
confidence: 99%